Examining the Constructs of Burnout, Compassion Fatigue, Secondary Traumatic Stress in Physicians Using Factor Analyses - Ahmed, Fadwa; Baruch, Jay; Armstrong, Paul (Frontiers in Public Health, 2022)
Background: Adverse affective experiences have been well-documented in healthcare providers. Research describes them under a variety of terms, including burnout, secondary traumatic stress (STS), and compassion fatigue (CF). The present study investigates the extent to which STS, CF, and burnout describe distinct phenomena in physicians. Methods: Surveys were mailed to all allopathic physicians with active Rhode Island medical licenses. 375 complete responses were received. The survey included common measures of STS, CF, and burnout. Confirmatory Factor Analysis (CFA) and Exploratory Factor Analysis (EFA) were conducted to assess underlying factor structure. Results: By CFA, all five a priori (1-,2-, and 3-factor) models of burnout, compassion fatigue, and secondary traumatic stress fail to demonstrate adequate model fit (Standardized Root Mean Square Residual > .10, Tucker-Lewis Index < .90). EFA with parallel analysis extracts four factors underlying the three burnout, STS, and CF measures. The four factors describe 54.3% of variance and can be described as (1) depressive mood; (2) primary traumatic stress-like symptoms; (3) responses to patients’ trauma; and (4) sleep disturbances. Conclusion: In spite of abundant discussion surrounding burnout, CF, and STS, adverse affective physician experiences are not well described by current conceptions of these terms. In the present study, measures of these terms do not uphold their theoretical factor structures. Future research might explore other terms and measures that may correspond to these factors.